East Indian Type - (:unkn) unknown (Watermaan, The hatter, Clothier and Draper, Trinidad, [Printed in England], 2008)
Photo of an East Indian woman dressed in traditional wear.
Colour: Brown, green, red and yellow hues; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; Ethnic costume--India; East Indians--Trinidad and Tobago; Jewelry--India; Hair ornaments--India; Nose ornaments--India; Bracelets--India; Necklaces--India